Rubella immunity among hospital personnel - Öneş, S. Ülker; Yalçın, Işık (The Turkish Journal of Pediatrics, 1983)
Rubella antibodies were investigated in 48 women of childbearing age working in the Children's Hospital of the Istanbul University Faculty of Medicine. In Turkey rubella vaccine is not available, and a protective level of antibody was found in 29.2% of the total cases. Outbreaks of rubella that occur in hospitals are of special concern, and the testing of all employess for the rubella antibody and the procurement of vaccine for immunization of those determined to be seronegative is recommended.
Keywords: hemagglutination-inhibition technique; rubella immunity; rubella vaccine